Hydrogen‐Peroxide‐Generating Electrochemical Scaffold Eradicates Methicillin‐Resistant Staphylococcus aureus Biofilms. Issue 6 (6th March 2019) - Raval, Yash S.; Mohamed, Abdelrhman; Zmuda, Hannah M.; Patel, Robin; Beyenal, Haluk
Abstract: Increasing rates of chronic wound infections caused by antibiotic‐resistant bacteria are a crisis in healthcare settings. Biofilms formed by bacterial communities in these wounds create a complex environment, enabling bacteria to persist, even with antibiotic treatment. Wound infections caused by methicillin‐resistant Staphylococcus aureus (MRSA) are major causes of morbidity in clinical practice. There is a need for new therapeutic interventions not based on antibiotics. Hydrogen peroxide (H2 O2 ) is a known antibacterial/antibiofilm agent, continuous delivery of which has been challenging. A conductive electrochemical scaffold (e‐scaffold) is developed, which is composed of carbon fabric that electrochemically reduces dissolved oxygen into H2 O2 when polarized at −0.6 VAg/AgCl, as a novel antibiofilm wound dressing material. In this study, the in vitro antibiofilm activity of the e‐scaffold against MRSA is investigated. The developed e‐scaffold efficiently eradicates MRSA biofilms, based on bacterial quantitation and ATP measurements. Moreover, imaging hinted at the possibility of cell‐membrane damage as a mechanism of action. These results suggest that an H2 O2 ‐generating e‐scaffold may be a novel platform for eliminating MRSA biofilms without using antibiotics and may be useful to treat chronic MRSA wound infections. Abstract : Chronic wound infections caused by antibiotic‐resistant bacteria are a healthcare crisis, creating the need for therapeutic interventions that do not include antibiotics. In this study, a conductive electrochemical scaffold that generates hydrogen peroxide, a known antibacterial/antibiofilm agent, is developed and its in vitro antibiofilm activity against Staphylococcus aureus is tested.